House ammonia exposure causes alterations in microbiota, transcriptome, and metabolome of rabbits - Li, Keyao; Pang, Shuo; Li, Zhechen; Ding, Xiaoning; Gan, Yating; Gan, Qianfu; Fang, Shaoming (Frontiers in Microbiology, 2023)
Pollutant gas emissions in the current production system of the livestock industry have negative influences on environment as well as the health of farm staffs and animals. Although ammonia (NH3) is considered as the primary and harmful gas pollutant in the rabbit farm, less investigation has performed to determine the toxic effects of house ammonia exposure on rabbit in the commercial confined barn. In this study, we performed multi-omics analysis on rabbits exposed to high and low concentration of house ammonia under similar environmental conditions to unravel the alterations in nasal and colonic microbiota, pulmonary and colonic gene expression, and muscular metabolic profile. The results showed that house ammonia exposure notably affected microbial structure, composition, and functional capacity in both nasal and colon, which may impact on local immune responses and inflammatory processes. Transcriptome analysis indicated that genes related to cell death (MCL1, TMBIM6, HSPB1, and CD74) and immune response (CDC42, LAMTOR5, VAMP8, and CTSB) were differentially expressed in the lung, and colonic genes associated with redox state (CAT, SELENBP1, GLUD1, and ALDH1A1) were significantly up-regulated. Several key differentially abundant metabolites such as L-glutamic acid, L-glutamine, L-ornithine, oxoglutaric acid, and isocitric acid were identified in muscle metabolome, which could denote house ammonia exposure perturbed amino acids, nucleotides, and energy metabolism. In addition, the widespread and strong inter-system interplay were uncovered in the integrative correlation network, and central features were confirmed by in vitro experiments. Our findings disclose the comprehensive evidence for the deleterious effects of house ammonia exposure on rabbit and provide valuable information for understanding the underlying impairment mechanisms.